Oxidative Regeneration of Carbonyl Compounds from Oximes by Pyridinium Fluorochromate: A Kinetic and Mechanistic Study - Sharma, Ajay; Vyas, Neha; Choudhary, A.; Prasadrao, PTSRK; Sharma, Vinita (Asian Journal of Chemistry, 2012)
The oxidative deoximination of several aldoximes and ketoximes by pyridinium fluorochromate, in dimethyl sulphoxide, exhibited a first order dependence on pyridinium fluorochromate. A Michaelis-Menten type kinetics was observed with respect to oximes. The oxidation of ketoximes is slower than that of aldoximes. The rates of oxidation of aldoximes correlated well in terms of Pavelich-Taft dual substituent-parameter equation. The low positive value of polar reaction constant indicated a nucleophilic attack by a chromate-oxygen on the carbon. The reaction is subjected to steric hindrance by the alkyl groups. The reaction of acetaldoxime has been studied in 19 different organic solvents. The solvent effect has been analyzed by multiparametric equations. A mechanism involving the formation of a cyclic intermediate, in the rate-determining step is suggested.